Beethoven and other figures - Naudin, Bernard, 1876-1946 (artist):::Creator:::::::::::: (M. Kaelin)
From Beethoven dessins de Bernard Naudin sur la Sonate en a mineur op. 57 dite 'Appassionata', limited edition, from set numbered 18-137 printed on Dutch paper made by Van Gelder. Cf-James Green